HLA Class I–sensitized Renal Transplant Patients Have Antibody Binding to SLA Class I Epitopes. Issue 8 (August 2019) - Martens, Gregory R.; Ladowski, Joseph M.; Estrada, Jose; Wang, Zheng-Yu; Reyes, Luz M.; Easlick, Juliet; Smith, Clarkson; Butler, James R.; Sidner, Richard A.; Eckhoff, Devin E.; Tector, Matthew; Tector, Joseph
Abstract : Background: Highly sensitized patients are difficult to match with suitable renal allograft donors and may benefit from xenotransplant trials. We evaluate antibody binding from sensitized patients to pig cells and engineered single allele cells to identify anti-human leukocyte antigen (HLA) antibody cross-species reactivity with swine leukocyte antigen (SLA). These novel testing strategies assess HLA/SLA epitopes and antibody-binding patterns and introduce genetic engineering of SLA epitopes. Methods: Sensitized patient sera were grouped by calculated panel reactive antibody and luminex single antigen reactivity profile and were tested with cloned GGTA1/CMAH/B4GalNT2 glycan knockout porcine cells. Pig reactivity was assessed by direct flow cytometric crossmatch and studied following elution from pig cells. To study the antigenicity of individual class I HLA and SLA alleles in cells, irrelevant sera binding to lymphoblastoid cells were minimized by CRISPR/Cas9 elimination of endogenous class I and class II HLA, B-cell receptor, and Fc receptor genes. Native HLA, SLA, and mutants of these proteins after mutating 144K to Q were assessed for antibody binding. Results: Those with predominately anti-HLA-B&C antibodies, including Bw6 and Bw4 sensitization, frequently have low pig reactivity. Conversely, antibodies eluted from porcine cells are more commonly anti-HLA-A. Single HLA/SLA expressing engineered cells shows variable antigenicity and mutation of 144K to Q reduces antibody binding for some sensitized patients. Conclusions: Anti-HLA antibodies cross-react with SLA class I in predictable patterns, which can be identified with histocompatibility strategies, and SLA class I is a possible target of genetic engineering.